Difference in distribution of the labor force by occupation for Sulaymaniyah governorate residents for the year 2013 - مصطفى عبد الله السويدي لبنى سمير يونس رفل ابراهيم طالب (College of Education for Women, 2019)
The study aims to elucidation Difference distribution of the labor force by occupation in Sulaymaniyah governorate for the year 2013 by result field study to governorate and explain different Spatially for labor force by career. and The study reaches That Executive staff and Scribes and who join their high ratio from Total the labor force And the second Grade to Specialists and Technicians and who join their While Occupied career Production workers and who join their and Operators Transport Equipment and Engaged the third Grade from the total labor force and Continued Height in career Executive staff and who join their on the male labor force too . while Production workers in second Grade for male labor force , while the female labor force Came Specialists and Technicians and who join their in the first Grade Followed by Executive staff and Scribes and who join their in second Grade . while came Lowest female labor force in Career Chief administrators and Managers and Workers in Agriculture And forests and Animal Husbandry and Hunting and Fishing Respectively .